The Role of Government in The Penta Helix Synergy Model on Halal Tourism Development and Economic Growth in Pahawang Island: Islamic Economic Perspective - Dania Hellin Amrina; Melinia; Rubhan Masykur (Jurnal Ekonomika dan Dinamika Sosial, 2023)
PERDA Lampung Province No. 6 of 2012 Pahawang Island has become a leading tourist destination for districts / cities, this cannot be separated from the charm of beauty that is on Pahawang Island. The high number of tourist visits, especially Pahawang Island, is one of the potentials in developing sharia tourism. Of course, in the development of the concept of sharia tourism, there needs to be cooperation between all interested parties in the tourism sector. In the penta helix synergy model, there are 5 elements or 5 stakeholders in the development of sharia tourism, namely the government, business people, communities, academics, and the media. Of the five elements contained in the penta helix synergy model, this research focuses on 1 element, namely the government, a discussion of the role of the government in developing sharia tourism and as a driver, regulator, and embracing other elements in working together to realize the concept of sharia tourism, especially on Pahawang Island